Assessing improvement capability in healthcare organisations: a qualitative study of healthcare regulatory agencies in the UK. (19th April 2018) - Furnival, Joy; Boaden, Ruth; Walshe, Kieran
Abstract: Objectives: Healthcare regulatory agencies are increasingly concerned not just with assessing the current performance of the organisations they regulate, but with assessing their improvement capability to predict their future performance trajectory. This study examines how improvement capability is conceptualised and assessed by healthcare UK regulatory agencies. Design: Qualitative analysis of data from six UK healthcare regulatory agencies was conducted. Three data sources were analysed using an a priori framework of eight dimensions of improvement capability identified from an extensive literature review. Setting: The focus of the research study was the regulation of hospital-based care, which accounts for the majority of UK healthcare expenditure. Six UK regulatory agencies that review hospital care participated. Participants: Data sources included interviews with regulatory staff ( n = 48), policy documents ( n = 90) and assessment reports ( n = 30). Intervention: None—this was a qualitative, observational study. Results: This research study finds that of eight dimensions of improvement capability, process improvement and learning, and strategy and governance, dominate regulatory assessment practices. The dimension of service-user focus receives the least frequency of use. It may be that dimensions which are relatively easy to 'measure', such as documents for strategy and governance, dominate assessment processes, or there may be gaps in regulatory agencies' assessment instruments, deficits of expertise in improvement capability, or practical difficulties in operationalising regulatory agency intentions to reliably assess improvement capability. Conclusions: The UK regulatory agencies seek to assess improvement capability to predict performance trajectories, but out of eight dimensions of improvement capability, two dominate assessment. Furthermore, the definition and meaning of assessment instruments requires development. This would strengthen the validity and reliability of agencies' assessment, diagnosis and prediction of performance trajectories, and support development of more appropriate regulatory performance interventions.